Seminoma in a gray brocket deer (Mazama gouazoubira) with unilateral cryptorchidism - Oliveira, Ayisa Rodrigues; Santos, Daniel Oliveira dos; Pereira, Fernanda M. A. M.; Carvalho, Thaynara Parente de; Vasconcelos, Izabela Magalhães Arthuso; Souza, Lucas dos Reis de; Silva, Laice Alves da; Gonçalves, Ana Beatriz Portes; Neto, Lauro L. S.; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2022)
Cryptorchidism is the incomplete descent of the testes and associated structures, and cryptorchid testes are more likely to develop testicular neoplasms, such as seminoma. This is the first report of a seminoma in a cryptorchid wild-caught gray brocket deer (Mazama gouazoubira). The animal developed a unilateral seminoma with classical histopathological findings and benign behavior. Six months after the orchiectomy the cervid presented a metatarsal opened fracture, dying during the orthopedic surgery. No macro or micrometric metastasis was observed at the necropsy.